Indochina - Wargnier, Regis, 1948- (Barcelona Sav, 1993)
This story is set in 1930, at the time when French colonial rule in Indochina is ending. An unmarried French woman who works in the rubber fields, raises a Vietnamese princess as if she was her own daughter. She, and her daughter both fall in love with a young French army officer, which will change both their lives significantly.
No recomendada para menores de 13 años
Idiomas : castellano y francés. Subt. : castellano y francés
Catherine Deneuve, Vincent Perez, Linh Dan Pham
Keywords: Películas cinematográficas -- DVD